Interaksi Sosial Antara Mahasiswa Jawa dan Sunda di Lingkungan Universitas Ivet Semarang - Khoirunnisak, Anis; Syakirin, Syakirin; Anggraeni, Nur; Anggraeni, Nur; Farichatunnisa, Farichatunnisa (Journal of Democratia, 2022)
and habits, so there are obstacles when communicating between ethnic Javanese and ethnic Sundanese. This can provide valuable views and insights in students' understanding of interculturality. The aim of this research is to find out how the interaction between Javanese PPKn students and Sundanese PPKn students at Ivet University Semarang and to find out what obstacles factors are experienced by Javanese ethnic PPKn students and Sundanese PPKn students in adapting to the campus environment. The research was conducted using qualitative research methods through a phenomenological approach which describes the social interactions of Javanese PPKn students and Sundanese PPKn students at Ivet University Semarang. The data sources used in this research are primary data sources, namely Ivet University PPKn student informants and there are secondary data sources which are other supporting sources. In collecting data, using in-depth interview techniques with students, campus observations, and communication documentation. The results of this research show that there are several challenges in social interaction between Javanese ethnic PPKn students and Sundanese ethnic PPKn students, there are also obstacles in understanding the customs and language of each group which can cause awkwardness in social interactions. Research also produces unique patterns in social interactions between Javanese and Sundanese students. Even though there are differences between the two in customs, language and traditions, the social interactions that occur tend to be harmonious. This is evident from the inclusive communication patterns. Apart from that, there are also aspects of solidarity and cooperation that exist very closely between ethnic Javanese PPKn students and PPKn students. The two student groups also jointly increase awareness of cultural diversity, support each other in academic and non-academic activities, and demonstrate strong social integration within the campus environment.